Dakwah Persaudaraan Islam dalam Short Movie - Linda Maulidah; Uwes Fatoni (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2019)
AbstractThe purpose of the reseach is to know a scene that represent existence of Islamic brotherhood, and how the scene of the Islamic brotherhood is viewed from the semiotics model of Charles sanders. This research is a qualitative study that examine the concept of the triangle meaning that is representment/sign, interpretant, and object. The results of this study find 14 representment scenes that represent Islamic brotherhood. As for the object representing Islamic brotherhood are nuances of a character's expression, or the circumstances being where people are. The interpretation obtained in the film shows the destructive factor and the booster of Islamic brotherhood from the attitudes indicated by the representament and object.AbstrakTujuan dari penelitian ini adalah untuk mengetahui adegan yang merepresentasikan eksistensi persaudaraan Islam, dan bagaimana pemandangan persaudaraan Islam dilihat dari model semiotika Charles Sanders. Penelitian ini merupakan penelitian kualitatif, yang mengkaji konsep segitiga yaitu representasi/tanda, interpretant, dan objek. Hasil penelitian ini menemukan 14 adegan representasi yang merepresentasikan persaudaraan Islam. Adapun objek yang merepresentasikan persaudaraan Islam adalah nuansa ekspresi seorang tokoh, atau keadaan di mana orang berada. Penafsiran yang diperoleh dalam film tersebut menunjukkan faktor perusak dan pendorong persaudaraan Islam dari sikap yang ditunjukkan oleh representasi dan objek.